Heavy metal detoxification by organic acids in barley seedlings - Jócsák Ildikó; Végvári György; Droppa Magdolna; Hungarian Congress on Plant Physiology, 8., 2005, Szeged (2005)
Changes in the amount of metal complexing organic acids were investigated in barley leaves during 0,1, 0,5, 1mM Ni treatment parallel with the measurement of Ni accumulation. The content of five organic acids (oxaloacetate, citrate, malate, succinate and fumarate) was measured in the leaves of barley seedlings hoping to identify them as parts of nickel detoxification mechanisms. Besides a 3 fold increase of citrate and malate, the amount of oxalate and fumarate increased by 5-6 fold. It was found that oxalate and fumarate are also take part in nickel complexation mechanisms.